Economic Outcomes for Transgender People and Other Gender Minorities in the United States: First Estimates from a Nationally Representative Sample - Christopher S. Carpenter; Maxine J. Lee; Laura Nettuno (Institute of Labor Economics (IZA), 2022)
We provide the literature's first estimates of economic outcomes for transgender people and other gender minorities in the United States using nationally representative data from the Household Pulse Survey. We find that transgender women – individuals who were assigned male at birth but who identify as female – are significantly less likely to be employed, have higher poverty rates, are more likely to have public health insurance, and report greater food insecurity compared to otherwise similar cisgender men. Differences between non-cisgender individuals who were assigned female at birth and cisgender women are smaller. Non-cisgender Black individuals fare significantly worse than non-cisgender white individuals, regardless of sex assigned at birth. Our results demonstrate the precarious economic position of gender minority populations in America.
Keywords: J1; 330; transgender; gender minority; economic outcomes; Household Pulse Survey